2018
DOI: 10.2106/jbjs.rvw.17.00161
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Critical Shoulder Angle and Shoulder Disease

Abstract: » In this review, we describe the history of the Critical Shoulder Angle (CSA), the utility of the CSA in identifying rotator cuff tears and glenohumeral osteoarthritis, and the association between the CSA and patient-reported outcomes. Additionally, we address some of the controversies surrounding the CSA with an updated literature review. » The CSA is the angle between the plane of the glenoid fossa (the line from the inferior edge of the glenoid to the superior edge of the glenoid) and a line drawn from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 43 publications
1
21
0
2
Order By: Relevance
“… 12 Watanabe et al 27 noted that patients with RCTs had a larger CSA compared with patients without RCTs ( P < .001). Li et al 14 similarly found that CSAs > 35° were associated with RCTs, due to the increased superior shear forces, whereas CSAs < 30° were associated with glenohumeral osteoarthritis, due to increased compressive forces across the glenohumeral joint. The value of this study is that it is the first to demonstrate the difference in the cuff-deficient shoulder function as it relates to radiographic parameters.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Watanabe et al 27 noted that patients with RCTs had a larger CSA compared with patients without RCTs ( P < .001). Li et al 14 similarly found that CSAs > 35° were associated with RCTs, due to the increased superior shear forces, whereas CSAs < 30° were associated with glenohumeral osteoarthritis, due to increased compressive forces across the glenohumeral joint. The value of this study is that it is the first to demonstrate the difference in the cuff-deficient shoulder function as it relates to radiographic parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The most common way is called the Critical Shoulder Angle (CSA), and measures the angle between the glenoid and the most lateral part of the acromion 194 . Larger CSA has been found to be associated with an increased risk of rotator cuff disease in some studies 166,194 , but not all studies have support for this association 25 . There are also other measures of the bony anatomy that may indicate an increased risk of rotator cuff tear, such as the greater tuberosity angle 58 and the Y-, G-and R-angles 233 .…”
Section: Prevalence and Predisposing Factors For Rotator Cuff Tearmentioning
confidence: 99%
“…Although in three recent studies [ 20 22 ], the correlation of CSA with rotator cuff diseases has been strongly criticized, the popularity of CSA has increased over time. Nonetheless, many points on CSA remain to be elucidated [ 23 ]. In a retrospective analysis of longitudinally collected data, Chalmers et al.…”
Section: Introductionmentioning
confidence: 99%